Gen Z's Utilization of Tiktok as a Tool to Improve English Vocabulary Mastery - Mudrikatussalamah, Nada; Hannah, Hannah; Fitria, Indah Nurul; Darsih, Endang (Proceedings Series on Social Sciences & Humanities, 2025)
The purpose of this study was to examine the use of the TikTok application as a medium to improve English vocabulary acquisition among Generation Z. Generation Z is very familiar with technology and social media, but many still have difficulty in expanding their English vocabulary. This study used a qualitative method using interviews with 10 respondents, consisting of students from the English education study program at Kuningan University who are included in Gen Z. The results of this study indicate that TikTok acts not only as an entertainment medium but also as an effective learning medium. Interesting educational content and a visual approach provided by the TikTok application will help respondents to remember and understand new vocabulary faster. User interaction with TikTok content such as liking, saving, and repeated pronunciation (repetition) contributes to vocabulary preservation. While TikTok has proven to be beneficial, it must also be noted how important it is to combine more structured learning methods to get optimal results. This study is expected to provide new knowledge to educators in using technology to improve the English learning process for Generation Z.